High speed heterostructure devices - Kiehl, Richard A.; Sollner, T. C. L. Gerhard (Semiconductors and semimetals, 1994)
Volume 41 includes an in-depth review of the most important, high-speed switches made with heterojunction technology. This volume is aimed at the graduate student or working researcher who needs a broad overview andan introduction to current literature. Key Features * The first complete review of InP-based HFETs and complementary HFETs, which promise very low power and high speed * Offers a complete, three-chapter review of resonant tunneling * Provides an emphasis on circuits as well as devices.